Blue Phosphorescent Organic Light-Emitting Devices with the Emissive Layer of mCP:FCNIr(pic). (19th June 2012) - Jang, Ji Geun; Ji, Hyun Jin
Abstract : New high-efficiency blue-light-emitting phosphorescent devices with 300 Å-thick emissive layer of N, N′-dicarbazolyl-3, 5-benzene [mCP] doped with 10 vol.% bis[(3, 5-difluoro-4-cyanophenyl)pyridine]iridium picolinate [FCNIr(pic)] were fabricated with the different treatments of hole and electron transport layers. In the experiments, a single layer of 1, 1-bis-(di-4-polyaminophenyl)cyclohexane [TAPC] and a double layer of N, N′-di(1-naphthyl)-N, N′-diphenylbenzidine [NPB] and mCP were used as hole transport layers (HTLs). In addition, 500 Å-thick double layers of tris-[3-(3-pyridyl)mesityl]borane [3TPYMB] and 4, 7-diphenyl-1, 10-phenanthroline [Bphen] were used as electron transport layers (ETLs) with various thickness combination of 3TPYMB/Bphen. Among the fabricated devices, the one using TAPC as an HTL and 3TPYMB(100 Å)/Bphen(400 Å) as an ETL showed best electroluminescent characteristics with a maximum quantum efficiency of 13.3% and a luminance of 950 cd/m 2 at 10 V. The color coordinates were (0.14, 0.22) on the Commission Internationale de I'Eclairage (CIE) chart, and the electroluminescent spectra showed the double-peak emissions at 458 nm and 483 nm.